Infant difficult behaviors in the context of perinatal biomedical conditions and early child environment - Sirvinskiene Giedre; Zemaitiene Nida; Zaborskis Apolinaras; Markuniene Egle; Jusiene Roma (BMC, 2012)
Abstract Background Problems experienced within the first year of an infant's life can be precursors of later mental health conditions. The purpose of this study was to examine the frequency and continuity of difficult behaviors in infants at 3 and 6 months of age and the associations of these difficulties with biomedical and psychosocial factors. Methods This study was a part of an ongoing prospective birth-cohort study. Study participants were 189 uniparous mothers and their full-term newborns. The index of infant difficult behavior was constructed. This index was then associated with the following factors: delivery mode, newborn function after birth, maternal emotional well-being, risk behavior, subjective evaluation of the quality of the relationship of the couple, and attitudes toward infant-rearing. Results Common difficult behaviors, including crying, sleeping and eating problems, were characteristic for 30.2% of 3 month old and for 22.2% of 6 month old full-term infants. The expression of infant difficult behaviors at the age of 3 months increased the likelihood of the expression of these difficulties at 6 months by more than 5 times. Factors including younger maternal age, poor prenatal and postnatal emotional well-being, prenatal alcohol consumption, low satisfaction with the couple's relationship before pregnancy, and deficiency of infant-centered maternal attitudes towards infant-rearing increased the likelihood of difficult behaviors in infants at the age of 3 months. Low maternal satisfaction with the relationship of the couple before pregnancy, negative emotional reactions of both parents toward pregnancy (as reported by the mother) and the deficiency of an infant-centered maternal attitude towards infant-rearing increased the likelihood of infant difficult behaviors continuing between the ages of 3 to 6 months. Perinatal biomedical conditions were not related to the difficult behaviors in infants. Conclusions Our study suggests that early onset of difficult behavior highly increases the risk for the continuation of difficult behavior during infancy. In general, the impact of prenatal psychosocial environment on infant behavior decreases from the ages of 3 to 6 months; however, some prenatal and preconceptional psychosocial factors have direct associations with the continuity of difficult behaviors through the first half-year of an infant's life.